Analysis of adsorption characteristics of diclofenac to sucrose-derived carbon spheres from aqueous solutions. Issue 6 (December 2021) - Yoo, Suk-Hyun; Kang, Jin-Kyu; Lee, Seung-Chan; Jang, Ho-Young; Kim, Song-Bae
Abstract: Diclofenac (DCF) is a nonsteroidal anti-inflammatory drug commonly found in wastewater and drinking water. The potential of carbon spheres (CSs) to serve as adsorbents in removal of DCF from water has been explored recently. However, glucose-derived CSs and cellulose-derived CSs reportedly have very low DCF adsorption capacities. Here, we describe the synthesis of sucrose-derived carbon spheres (SDCSs) for adsorption of DCF from aqueous solutions. The physicochemical properties of the SDCSs were characterized using various instrumental techniques. The SDCSs were spherical particles with an average size of 224.2 ± 19.5 nm, a point of zero charge (pHpzc ) of 3.14, a Brunauer–Emmett–Teller specific surface area of 239.3 m 2 /g, a total pore volume of 0.142 cm 3 /g, and an average pore diameter of 2.38 nm. The adsorption characteristics of the SDCSs were investigated under batch conditions by varying the solution pH, reaction time, initial DCF concentration, and temperature. Adsorption experiments demonstrated that the DCF adsorption capacity was highest at an initial pH of 5 and decreased gradually as the pH was increased to 11. X-ray photoelectron spectroscopy spectra of the SDCSs before and after DCF adsorption indicate that DCF adsorption to the SDCSs occurred through hydrogen-bond formation and π-π interactions. According to the pHpzc value and experimental pH data, repulsive electrostatic interactions between the negatively charged SDCSs and negatively charged DCF resulted in a decrease of DCF adsorption capacity as pH increased. Kinetic and equilibrium data showed that DCF adsorption to the SDCSs reached equilibrium at 6 h, with a maximum adsorption capacity of 531.5 mg/g, which was far higher than glucose-derived CSs and cellulose-derived CSs. DCF adsorption to the SDCSs was endothermic, increasing with increasing temperature from 10 ℃ to 40 ℃. Five adsorption-desorption cycles demonstrated that the SDCSs can be regenerated with methanol and reused in DCF adsorption. This study demonstrates that SDCSs have a high adsorption capacity and reusability for adsorption of DCF from aqueous solutions. Graphical Abstract: ga1 Highlights: The equilibration time for the DCF adsorption to the SDCNs was 6 h. The maximum DCF adsorption capacity of the SDCNs was 531.5 mg/g from Langmuir model. DCF adsorption to the SDCNs was endothermic, increasing with increasing temperature. The SDCNs could be successfully regenerated and reused with methanol for DCF adsorption. The SDCNs had far higher DCF adsorption capacity than cellulose- and glucose-derived carbon spheres.